PENGEMBAGAN DESAIN BENTUK DAN FINISHING PADA UKM GITAR - Noviani, Leny; Nugroho, Jonet Ariyanto; Wahida, Adam (Universitas Negeri Yogyakarta, 2013)
The purpose of this activity are: (1) to develop a more varieddesigns; (2) develop the capability of finishing techniques; (3) improvementof production management and expand the marketing network. The methodused in this service activity is socialization, training, and mentoring.Through the dedication program has generated forms are more varied guitarproducts. Crafters are able develop designs shapes and finishing with aclassic decorative motifs and abstract. Through the application of finishingtechniques using decorative motifs, crafters also has produced guitars thatare visually more appealing. Efforts to expand the marketing networkcrafting guitars through a media campaign web blog.